L’astensione dal voto dell’amministratore di società per azioni in conflitto di interessi da dovere a diritto (Milan Law Review, 2021)
The current regulation of the conflict of interests in corporations raises a number of issues arising from the difficult coexistence between, on the one hand, the choice of eliminating the express provision of the duty to abstain from voting by the administrator holding the interest, and, on the other hand, that of considering invalid the resolution adopted with his relevant vote, given its potential damage to the company. This paper attempts to overcome the potential contradiction between a vote, that of the administrator in conflict of interest, apparently lawful and, at the same time, at least potentially invalid, by observing that abstention from voting, originally a duty, has over time become lawful.
Keywords: corporations; conflict of interest; duty of abstention; invalid resolution